Building Entrepreneurial Capacity among Fisherwomen through Fish Meatball Production Training in Coastal Communities - Sumiati Tahir; Valentino Aris; Rezky Nurfadillah; Asmayanti Asmayanti; Anggi Kemalasari (PT. Global Research Collaboration, 2025)
Mattiro Uleng Village, a coastal fishing community in Pangkajene and Kepulauan Regency, holds abundant marine resources, yet its utilization remains limited to selling raw fish without further processing. This dependence on unprocessed fish sales has led to fluctuating family incomes, particularly for fishermen’s wives, who rely on their husbands’ catch. This community service program was designed to empower fishermen’s wives in Mattiro Uleng by enhancing their skills in producing value-added fish-based products, specifically fish meatballs, as a means of economic diversification and fostering independent entrepreneurship. The program implementation involved a combination of theoretical knowledge sessions, practical workshops on fish meatball processing, and training in both online and offline marketing strategies. A participatory approach was adopted to actively engage participants throughout the process. Evaluation results showed a significant improvement in participants’ skills, with fish meatball-making competency increasing from 30% to 90%, and marketing knowledge rising from 10% to 75%. This program successfully equipped the participants with practical knowledge, boosted their confidence, and sparked motivation for initiating fish-based culinary enterprises.